2019
DOI: 10.1002/cncr.31838
|View full text |Cite
|
Sign up to set email alerts
|

Cancer disparities in people with HIV: A systematic review of screening for non‐AIDS–defining malignancies

Abstract: BACKGROUND People with the human immunodeficiency virus (PWHIV) have improved survival because of the advent of antiretroviral therapy. Consequently, PWHIV experience higher rates of non-acquired immunodeficiency syndrome-defining malignancies (NADMs). Previous studies have demonstrated worsened cancer-specific survival in PWHIV, partly because of advanced cancer stage at diagnosis. The objective of the current systematic review was to evaluate screening disparities for NADMs among PWHIV. METHODS The PubMed,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 37 publications
1
20
0
1
Order By: Relevance
“…In an age without widespread use of ART, active management of other non-AIDS-defining cancers (NADCs) was less common, for the life expectancy of PLWH was relatively short [ 5 ]. As survival has improved [ 6 8 ], NADCs have consistently been reported, as reflected in the higher risk for cancer in PLWH compared to the general population [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…In an age without widespread use of ART, active management of other non-AIDS-defining cancers (NADCs) was less common, for the life expectancy of PLWH was relatively short [ 5 ]. As survival has improved [ 6 8 ], NADCs have consistently been reported, as reflected in the higher risk for cancer in PLWH compared to the general population [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Certain cancers such as breast, cervical, and lung cancers are screened routinely as early detection improves mortality. In PLWH, these malignancies are often found at more advanced stages when compared to the general population, possibly due to a lack of adherence to screening programs [32], or possibly due to under-insurance, low income, and education within this population [33]. Cervical cancer is one of the most common ADCs, and progression of the neoplasm to a malignant state likely reflects both delayed clearance of the Human Papilloma Virus (HPV) for extended periods [34], as well as rapid progression from pre-malignant cervical carcinoma in situ (CIN) to invasive cervical cancer [35].…”
Section: Discussionmentioning
confidence: 99%
“…The need for screening programs is evident and not all those at risk receive this. It has been shown that access to and delivery of cancer screening are related to social determinants of health (insurance status, access to health care, education, income level) and that these barriers need to be addressed to improve cancer screening in PLWH (Corrigan, Wall, Bartlett, & Suneja, 2019).…”
Section: Question 1: What Are the Epidemiological And Clinical Featurmentioning
confidence: 99%